Strategic marketing and innovation for Indian MSMEs - Srinivasan, R., Prof; Lohith, C. P. (Springer, 2017)
This book investigates how strategic marketing is influencing organizations' innovation performance. It presents a structured study conducted on micro, small and medium enterprises (MSMEs) to identify the correlation between innovation and strategic marketing in both Indian manufacturing and service organizations. Strategic marketing, which achieves excellence in organizations, is at the heart of improving productivity, profitability and market sustainability, while also supplying organizations a much sought-after competitive advantage. It has been observed that strategic marketing can significantly help any manufacturing firm to attain the required level of growth, and can specifically be used by Indian firms as a means of deriving differential advantages. Indian organizations that pursue more traditional approaches to strategy are now feeling the intense market pressure to modify their policy with respect to quality. The result has been a shift to 'Strategy with Innovation'. As market competition has again increased, providing quality products and services alone is no longer sufficient; companies are additionally expected to provide products with a touch of innovation to attract customers. This calls for innovation in terms of products, processes, technologies, systems and practically every other area of an organization, which can only be achieved by combining strategies and innovation. This book identifies the variables of strategic marketing that can help companies significantly boost their innovation performance, making it a valuable resource for students, researchers, professionals and policymakers alike.
Keywords: Small business marketing -- India.; Small business -- Technological innovations -- India.; India.; elektronické knihy; electronic books